Potensi Wisata Makan Durian Musuk Boyolali: Studi Kasus Tentang Pengalaman Wisatawan Dan Dampaknya Terhadap Ekonomi Lokal - Emmelia Nadira Satiti; Kris Cahyani Ermawati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The potential for durian culinary tourism in Kembangsari Village, Musuk District, Boyolali Regency is a major concern in developing local tourism. This study assesses tourist experiences and their impact on the local economy. Through SWOT analysis, the main strengths are found in high quality durian, relatively cheap prices offered, and a beautiful atmosphere, namely the durian garden. However, challenges such as the lack of tourism infrastructure and dependence on the durian season need to be overcome so that this tourism can have a significant impact on improving the economy of the surrounding community. Development opportunities include diversifying tourism experiences and strengthening promotions.